THE RELATIONSHIP BETWEEN DYNAMIC KINETIC BALANCE AND THE ACCURACY OF SHORT PASSING IN FEMALE FUTSAL PLAYERS - Majeed Hameed Majeed; Riyadh Jumaah Hasan; Saleh Ali Danhash (Proximus Journal Publishing, 2025)
Futsal is a sport that requires a high level of technical skill, particularly in short and accurate passing, which is heavily reliant on dynamic kinetic balance. This research aims to study the relationship between dynamic kinetic balance and the accuracy of short passing in futsal. It seeks to determine the extent to which improving dynamic kinetic balance impacts the accuracy of short passes and ball control. This research contributes to: enhancing the technical performance of futsal players; shedding light on the kinetic factors that influence short passing accuracy; and assisting coaches in designing training programs to improve dynamic kinetic balance. Based on field observations of the performance of female players from Al-Zawraa Futsal Club, the researchers noted a clear deficiency in the execution of short passing among most players, despite the great importance of this skill in futsal. The researchers attributed this weakness to a deficit in the physical quality of dynamic kinetic balance, which is a vital physical attribute that directly affects skillful performance. From this perspective, the research aimed to uncover the relationship between dynamic kinetic balance and the accuracy of short passing performance in futsal. Hypothesis: The research hypothesis was that there is a statistically significant relationship between dynamic kinetic balance and the accuracy of short passing. The researchers found a correlation between these two variables. Based on these findings, the researchers recommended focusing on developing dynamic kinetic balance in players through training programs that enhance fundamental futsal skills, due to its positive impact on improving short passing accuracy
Keywords: Dynamic Kinetic Balance; Accuracy; Short Passing